肝细胞生长因子诱导敏感非小细胞肺癌细胞对吉非替尼耐药及机制的研究 (Zhongguo Fei Ai Za Zhi, 2013)
BACKGROUND AND OBJECTIVE: Previous studies have reported that Met might be related to gefitinib resistance in non-small cell lung cancer (NSCLC). The present study aims to explore the mechanism of hepatocyte growth factor (HGF)-induced gefitinib resistance in different gene types of sensitive NSCLC in vitro. METHODS: The PC-9 and H292 cell lines were chosen and induced by HGF. The cell survival was measured using MTT assay, the cell cycle distribution was measured using PI assay, and cell apoptosis with an Annexin V-PE assay, respectively. The c-Met and p-Met protein expression was determined via Western blot analysis. RESULTS: Gefitinib inhibited the growth of PC-9 and H292 cells in a dose-dependent manner. The concentration-survival curves of both cell lines shifted to the right when induced with HGF. HGF did not affect PC-9 and H292 cell proliferation. The cell also had a higher cell survival rate when treated with HGF and gefitinib compared with that under gefitinib alone (P < 0.05). The apoptotic rate and cell cycle progression showed no significant difference between the HG and G group (P > 0.05). HGF stimulated Met phosphorylation in the PC-9 and H292 cells. Gefitinib inhibited the HGF-induced Met phosphorylation in PC-9 cells, but not in H292 cells. CONCLUSION: HGF induces gefitinib resistance in PC-9 and H292 cells. HGF-induced Met phosphorylation may be an important mechanism of gefitinib resistance in sensitive NSCLC.